The impact of usage experience and input modality on trust experience and cognitive load in older adults - Huang, Hui; Hou, Guanhua (Frontiers in Computer Science, 2025)
Trust experience plays a pivotal role in human–computer interaction, particularly for older adults, where it serves as a critical psychological threshold for technology adoption and sustained usage. Against the backdrop of increasingly diverse intelligent interaction modalities, trust directly influences older adults’ initial acceptance and long-term reliance on technological systems. This study focuses on the interactive effects of users’ experience and input modality on trust experience and cognitive load in the elderly. Employing a 2 (prior experience: experienced vs. inexperienced) × 3 (input modality: touch, speech, eye control) mixed experimental design. Following each task, participants completed NASA-TLX scales and trust perception questionnaires, supplemented by eye-tracking data to quantify cognitive load and behavioral patterns. The results showed that (1) Experience-dependent divergence in trust perception: Experienced older adults exhibited higher trust in touch input, attributable to established press-response mental models from prior device usage, while inexperienced users preferred speech input due to its alignment with natural conversational paradigms. (2) Cognitive load mediation effect: Although voice input reduces the learning cost of user interfaces for inexperienced elderly users (NASA-TLX is 24% lower than touch), recognition errors can cause a sharp drop in trust; This study reveals that the trust experience of elderly users is influenced by both usage experience and input methods, with cognitive load being a key mediating factor. In terms of design, the touch physical metaphor should be retained for experienced elderly users, and the voice fault tolerance mechanism should be strengthened for inexperienced elderly users, while reducing technical anxiety by enhancing operational visibility.